(untitled) (Journal of Dhaka Medical College, 2011)
Diabetes mellitus is one of the most important modifiable risk factors for ischemic stroke.Cigarette smoking is a risk factor for atherosclerotic disease. There is a strong relationship between diabetes mellitus and cigarette smoking with ischemic stroke. A case control study was designed to see the association of diabetes mellitus and cigarette smoking with ischaemic stroke. The study was done from January 2009 to December 2009. Sixty subjects were selected as study population which were taken from Dhaka medical college hospital, Dhaka. Among them 30 were diagnosed case of ischemic stroke and 30 were age and sex matched control. The study showed that 33.33% patients of case group and 10 % respondents of control group had diabetes mellitus. It also revealed that 56.66% of case group and 53.33% of control group were smoker and the mean duration of smoking was 27.41 ± 2.98 years in case group and 15.63 ± 2.85 years in control group. The study suggests that diabetes mellitus is significantly associated with ischemic stroke and longer duration of smoking is also associated with ischaemic stroke. Key words: Ischemic stroke; cigarette smoking; diabetes mellitus. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8565 J Dhaka Med Coll. 2011; 20(1) : 12-14